Frequency-dependent functional alterations in people living with HIV with early stage of HIV-associated neurocognitive disorder - Wang, Wei; Liu, Dan; Wang, Yuanyuan; Li, Ruili; Liu, Jiaojiao; Liu, Mingming; Wang, Huasong; Li, Hongjun (Frontiers in Neuroscience, 2023)
Background: HIV enters the brain soon after seroconversion and causes HIV associated neurocognitive disorders (HAND). However, the impairment is insidious at the early stage and the pathogenesis is still unclear. Objectives: To explore functional integration and segregation changes at the early stages of HAND, voxel-level indices of regional homogeneity (ReHo), amplitude of low-frequency fluctuations (ALFF), and voxel-mirrored homotopic connectivity (VMHC) under two different frequency bands (slow-5:0.01–0.027 Hz; slow-4:0.027–0.073 Hz) were analyzed. Methods: Ninety-eight people living with HIV (PLWH) and 44 seronegative controls underwent resting-state functional magnetic resonance imaging. Also, all PLWHs underwent neuropsychological and daily functioning tests. The main effect of the group and the interaction between the group and frequency band were investigated. Finally, the relationship between the altered indices and the cognitive domains was explored. Results: A significant group-by-frequency interaction was demonstrated in the right thalamus for ReHo; for VMHC, the interaction was observed in the bilateral precuneus and paracentral gyrus. The post-hoc Bonferroni test indicated that the alteration of ReHo and VMHC could only be detected in slow-5. PLWH showed significantly reduced ALFF in both the frequency bands in the right occipital gyrus and right calcarine. Moreover, some altered functional integration and segregation indices are related to impaired cognitive function. Conclusion: PLWH displayed aberrant functional integration and segregation at the early stages of HAND, which is linked to cognitive function. The frequency band of slow-5 might be more sensitive for detecting insidious damage at an early stage.